Cuprous phosphide-coated lithium nickel cobalt manganese oxide positive electrode material as well as preparation method and application thereof
By generating a copper phosphide cladding layer on the surface of nickel-cobalt-manganate, the structural transformation and electrolyte oxidation and decomposition of the positive electrode material of lithium-ion batteries are solved, and the circulation stability and battery performance of the material are improved.
Patent Information
- Application Number
- CN202510546313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-07-25
AI Technical Summary
In practical applications, the cathode material of LiNi1-x-yCoxMnyO2 (NCM) of lithium-ion battery has problems such as transformation of layered structure into rock salt structure and disordered spinel structure, oxidation and decomposition of electrolyte on the positive electrode surface, and transition metal ion dissolution, resulting in a reduction in cyclic stability.
The copper phosphide cladding layer is formed on the surface of nickel-cobalt-manganese oxide. The nickel-cobalt-manganese oxide is dispersed in the copper ion salt solution by the preparation method, and the ammonium fluoride solution is added dropwise to produce NH4CuF3. After heat treatment, copper fluoride is formed. Then, phosphine is introduced under an inert atmosphere to reduce the copper phosphide to form a uniform cladding layer.
The copper phosphide cladding barrier electrolyte is in direct contact with nickel-cobalt lithium manganate, inhibits oxidation and decomposition, reduces transition metal dissolution, stabilizes the interface structure, and improves battery circulation and overall performance.
Smart Images

Figure CN120364762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cathode materials, and particularly relates to a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] The lithium ion battery cathode material LiNi 1-x-y Co x Mn y O2 (NCM, lithium nickel cobalt manganese oxide) faces many problems in practical applications, such as the transformation of the layered structure into the rock salt structure and the disordered spinel structure, the oxidative decomposition of the electrolyte on the surface of the cathode, the dissolution of transition metal ions, and HF corrosion. These side reactions occurring at the interface between the cathode material and the electrolyte reduce the cycle stability of the lithium ion battery. Therefore, strengthening the stability at the interface between the NCM material and the electrolyte is the key to improving the cycle life of the NCM cathode material. Summary of the Invention
[0003] The purpose of the present invention is to provide a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, a preparation method thereof, and an application thereof, which can eliminate the surface defects of lithium nickel cobalt manganese oxide and reduce the surface phase change of the material, while blocking the direct contact between the lithium nickel cobalt manganese oxide cathode material and the electrolyte, inhibiting the oxidative decomposition of the electrolyte on the surface of the cathode, and thus achieving the effect of improving the cycle stability of the NCM cathode material.
[0004] In order to achieve the above purpose, the technical scheme adopted by the present invention is as follows: In the first aspect, the present invention discloses a preparation method of a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, which includes: Disperse lithium nickel cobalt manganese oxide in a copper ion salt solution to obtain a first mixed solution; Dropwise add an ammonium fluoride solution to the first mixed solution and continuously stir to obtain a second mixed solution; Centrifuge the second mixed solution, take the precipitate for washing and drying to obtain a precursor, which includes lithium nickel cobalt manganese oxide and NH4CuF3 generated by reaction on the surface of the lithium nickel cobalt manganese oxide; Perform a first heat treatment on the precursor in an inert atmosphere, and NH4CuF3 decomposes on the surface of the lithium nickel cobalt manganese oxide to generate copper fluoride; Then perform a second heat treatment on the precursor in an inert atmosphere and under the condition of introducing phosphine, and the copper fluoride is reduced by phosphine to generate copper phosphide, that is, a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material is obtained.
[0005] Further, the copper ion salt solution is a copper nitrate solution, a copper sulfate solution or a copper chloride solution; the concentration of the copper ion salt solution is 0.001 mol / L to 0.01 mol / L; in the first mixed solution, the molar ratio of lithium nickel cobalt manganate to copper ions is 25 to 76:1.
[0006] Further, the concentration of the ammonium fluoride solution is 0.01 mol / L to 0.05 mol / L; in the second mixed solution, the molar ratio of ammonium fluoride to copper ions is 2 to 4:1.
[0007] Further, the heating temperature of the first heat treatment is set to 250 °C to 300 °C, and the heat preservation time is set to 120 min to 420 min.
[0008] Further, the heating temperature of the second heat treatment is set to 220 °C to 300 °C, and the heat preservation time is set to 120 min to 240 min.
[0009] Further, the molar ratio of phosphine to copper ions is 3 to 10:1.
[0010] Further, performing the second heat treatment on the precursor under an inert atmosphere with phosphine introduced specifically includes: placing sodium dihydrogen phosphite and the precursor after the first heat treatment in a first crucible and a second crucible respectively, then placing the first crucible and the second crucible in a heating furnace at a preset distance, with the first crucible located at the upwind position, and finally performing the second heat treatment under an inert atmosphere. Sodium dihydrogen phosphite decomposes upon heating to produce phosphine, and copper fluoride is reduced by phosphine to form cuprous phosphide.
[0011] Further, after the addition of the ammonium fluoride solution is completed, stirring is continued for 60 min to 180 min under the condition of a rotation speed of 300 rpm to 900 rpm.
[0012] In a second aspect, the present invention discloses a cuprous phosphide-coated lithium nickel cobalt manganate cathode material, which is prepared by using the above-mentioned preparation method of the cuprous phosphide-coated lithium nickel cobalt manganate cathode material, and includes lithium nickel cobalt manganate and cuprous phosphide coated on the surface of lithium nickel cobalt manganate.
[0013] In a third aspect, the present invention discloses an application of the above-mentioned cuprous phosphide-coated lithium nickel cobalt manganate cathode material in a lithium-ion battery.
[0014] The present invention has the following unexpected beneficial effects: In the preparation method of the present invention, a cuprous phosphide coating layer is formed on the surface of lithium nickel cobalt manganese oxide. On the one hand, the cuprous phosphide coating layer has good conductivity, and its discharge voltage platform is below 1.5V. It will not react within the charge-discharge window of lithium nickel cobalt manganese oxide and can stably exist on the surface of lithium nickel cobalt manganese oxide during the charge-discharge cycle of lithium nickel cobalt manganese oxide. It can block the direct contact between lithium nickel cobalt manganese oxide and the electrolyte, weaken the erosion of the electrolyte on lithium nickel cobalt manganese oxide, inhibit the oxidation and decomposition of the electrolyte on the surface of lithium nickel cobalt manganese oxide, reduce the dissolution of transition metals, thereby improving the cycle performance of lithium nickel cobalt manganese oxide. On the other hand, due to the existence of the cuprous phosphide coating layer, the surface defects of lithium nickel cobalt manganese oxide can be eliminated and the surface phase change of lithium nickel cobalt manganese oxide can be reduced, stabilizing the interface structure, thereby improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention.
[0016] Figure 1 The flow chart showing the preparation method of the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material according to the embodiment of the present invention is shown.
[0017] Figure 2 The layout diagram showing the sodium dihydrogen phosphate and the precursor after the first heat treatment in the heating furnace during the second heat treatment according to the embodiment of the present invention is shown.
[0018] Figure 3 The diagram showing the cycle performance test results of the products of Example 1, Example 2 and the comparative example of the present invention is shown. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0019] The following will describe the embodiments of the present invention with reference to the drawings and preferred embodiments. Those skilled in the art can easily understand the other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for explaining the present invention, rather than for limiting the protection scope of the present invention.
[0020] It should be noted that the drawings provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner. The drawings only show the components related to the present invention, rather than being drawn according to the number, shape and size of the components in actual implementation. The type, quantity and ratio of each component in actual implementation can be arbitrarily changed, and the component layout type may also be more complex.
[0021] In one embodiment, as shown in Figure 1 Figure 1 , the present invention provides a method for preparing a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, which comprises the following steps: S1, dispersing lithium nickel cobalt manganese oxide in a copper ion salt solution to obtain a first mixed solution.
[0022] S2, dropping an ammonium fluoride solution into the first mixed solution and continuously stirring to obtain a second mixed solution.
[0023] S3, centrifuging the second mixed solution, taking the precipitate for washing and drying to obtain a precursor, which comprises lithium nickel cobalt manganese oxide and NH4CuF3 formed by reaction on the surface of the lithium nickel cobalt manganese oxide.
[0024] S4, performing a first heat treatment on the precursor under an inert atmosphere, and NH4CuF3 decomposes on the surface of the lithium nickel cobalt manganese oxide to generate copper fluoride.
[0025] S5, performing a second heat treatment on the precursor after the first heat treatment under an inert atmosphere and with phosphine introduced, and the copper fluoride is reduced by phosphine to generate copper phosphide, that is, the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material is obtained.
[0026] When the ammonium fluoride solution is added to the copper ion salt solution, ammonium fluoride reacts with copper ions to generate NH4CuF3. The specific reaction formula is: Cu 2+ +NH4 + +3F - →NH4CuF3. The lithium nickel cobalt manganese oxide particles serve as a heterogeneous surface, reducing the nucleation barrier of the NH4CuF3 crystal nuclei. According to the nucleation theory, the heterogeneous surface of the lithium nickel cobalt manganese oxide particles provides additional sites for nucleation, making it easier for NH4CuF3 to aggregate on the surface of the lithium nickel cobalt manganese oxide particles to form crystal nuclei, thereby forming a precursor of the coating layer on the surface of the lithium nickel cobalt manganese oxide and laying a foundation for the subsequent formation of a uniform coating layer.
[0027] When performing the first heat treatment, under an inert atmosphere, NH4CuF3 undergoes a decomposition reaction. The specific reaction formula is: NH4CuF3→CuF2+NH3+HF.
[0028] High temperature breaks the chemical bonds of NH4CuF3, decomposes to generate copper fluoride (CuF2), and adheres to the surface of the lithium nickel cobalt manganese oxide in a solid state, completing the transformation from the precursor to the intermediate product and creating conditions for the next step of generating copper phosphide.
[0029] When performing the second heat treatment, phosphine (PH3) serves as a reducing agent to reduce copper fluoride (CuF2) to copper phosphide (Cu3P). The specific reaction formula is: 6CuF2+8PH3→2Cu3P+3P2H4+12HF.
[0030] The phosphorus element in phosphine is in a low-valence state and has strong reducing properties. It can capture oxygen from copper fluoride, reduce the valence state of the copper element, and generate the target product cuprous phosphide. A coating layer is successfully constructed on the surface of lithium nickel cobalt manganese oxide to obtain cuprous phosphide-coated lithium nickel cobalt manganese oxide positive electrode material.
[0031] The preparation method of the present invention generates a cuprous phosphide coating layer on the surface of lithium nickel cobalt manganese oxide. On the one hand, the cuprous phosphide coating layer has good conductivity, the discharge voltage platform is below 1.5V, and it will not react within the charge and discharge window of lithium nickel cobalt manganese oxide. It can stably exist on the surface of lithium nickel cobalt manganese oxide during the lithium nickel cobalt manganese oxide cycle, block the direct contact between lithium nickel cobalt manganese oxide and the electrolyte, weaken the corrosion of the electrolyte on the lithium nickel cobalt manganese oxide, inhibit the oxidative decomposition of the electrolyte on the surface of lithium nickel cobalt manganese oxide, and reduce the dissolution of transition metals, thereby achieving the effect of improving the cycle performance of lithium nickel cobalt manganese oxide. On the other hand, due to the presence of the cuprous phosphide coating layer, the surface defects of lithium nickel cobalt manganese oxide can be eliminated and the surface phase change of lithium nickel cobalt manganese oxide can be reduced, and the interface structure can be stabilized, thereby improving the overall performance of the battery.
[0032] As a preferred embodiment of the present invention, the copper ion salt solution is a copper nitrate solution, a copper sulfate solution or a copper chloride solution; the concentration of the copper ion salt solution is 0.001 mol / L~0.01 mol / L; in the first mixed solution, the molar ratio of lithium nickel cobalt manganese oxide to copper ions is 25~76:1.
[0033] In this preferred embodiment, it is clear that the concentration of the copper ion salt solution is 0.001mol / L~0.01mol / L. This concentration range is crucial for the smooth progress of the reaction and product quality control. If the concentration is too low, the copper ion content is small, which may lead to insufficient amount of NH4CuF3 generated, and it is impossible to form a complete and uniform coating layer; if the concentration is too high, the reaction may be too violent and difficult to control, resulting in uneven coating thickness and even agglomeration. Within this concentration range, it can ensure that copper ions react fully with ammonium fluoride to form a coating precursor of good quality on the surface of lithium nickel cobalt manganese oxide, thereby laying the foundation for the subsequent generation of high-quality cuprous phosphide coating layers.
[0034] Meanwhile, the molar ratio of lithium nickel cobalt manganate to copper ions in the first mixed solution is limited to 25-76:1, which has a positive impact on the performance of the final cathode material. The appropriate molar ratio ensures that the reaction between copper ions and lithium nickel cobalt manganate reaches equilibrium, resulting in a moderate coverage of the copper phosphide coating on the surface of lithium nickel cobalt manganate. When the molar ratio is within this range, the formed coating can effectively block the direct contact between the electrolyte and lithium nickel cobalt manganate, reduce the dissolution of transition metals, inhibit the oxidation and decomposition of the electrolyte, and improve the cycling performance of the material; at the same time, it will not affect the conductivity and lithium ion diffusion rate of the material due to an overly thick coating, thus optimizing the charge and discharge performance and stability of the battery as a whole.
[0035] As a preferred embodiment of the present invention, the concentration of the ammonium fluoride solution is 0.01 mol / L - 0.05 mol / L; in the second mixed solution, the molar ratio of ammonium fluoride to copper ions is 2-4:1. With such settings, it can ensure that the reaction to generate NH4CuF3 proceeds efficiently and orderly. Within this concentration and ratio range, copper ions and ammonium fluoride react fully, avoiding the residue of copper ions and incomplete reaction due to insufficient ammonium fluoride, which affects the generation amount and quality of the coating precursor; and preventing the increase of impurities in the solution and the complexity of the reaction system difficult to control due to excessive ammonium fluoride. Furthermore, it ensures the uniform and stable formation of a sufficient amount of NH4CuF3 coating precursor on the surface of lithium nickel cobalt manganate, laying a solid foundation for the subsequent generation of a high-quality copper phosphide coating.
[0036] As a preferred embodiment of the present invention, the heating temperature of the first heat treatment is set to 250°C - 300°C, and the holding time is set to 120 min - 420 min.
[0037] Within this temperature and time range, it can ensure that NH4CuF3 in the precursor is fully decomposed into copper fluoride. If the heating temperature is too low or the holding time is too short, NH4CuF3 will not be decomposed completely, and some undecomposed NH4CuF3 will remain on the surface of lithium nickel cobalt manganate, which will not only affect the subsequent generation of copper phosphide but also may trigger side reactions during the charge and discharge process of the battery, reducing the performance of the cathode material. When the heating temperature is 250°C - 300°C and the holding time is 120 min - 420 min, NH4CuF3 can be decomposed more completely, providing sufficient and pure copper fluoride raw materials for the next step of generating copper phosphide.
[0038] Moreover, appropriate heat treatment conditions also help to optimize the distribution and crystallization state of copper fluoride on the surface of lithium nickel cobalt manganese oxide, thereby affecting the structure of the final copper phosphide coating layer. Within this temperature range, the crystallization process of copper fluoride is relatively stable, and a uniform and dense structure can be formed on the surface of lithium nickel cobalt manganese oxide. By reasonably controlling the holding time, the crystallization growth process of copper fluoride can proceed fully, avoiding incomplete crystallization due to too short time or problems such as excessive crystal growth and agglomeration caused by too long time. This uniform and dense copper fluoride structure can be converted into a copper phosphide coating layer with excellent performance after being reduced by phosphine, enhancing the protection effect on lithium nickel cobalt manganese oxide.
[0039] As a preferred embodiment of the present invention, the heating temperature of the second heat treatment is set to 220°C to 300°C, and the holding time is set to 120 min to 240 min.
[0040] Such settings provide suitable conditions for the reduction of copper fluoride by phosphine to generate copper phosphide. This temperature range can make phosphine have sufficient activity to react fully with copper fluoride, ensuring that the reduction reaction proceeds efficiently in the direction of generating copper phosphide. If the temperature is too low or the time is too short, the activity of phosphine is insufficient and the reduction of copper fluoride is incomplete, resulting in more copper fluoride remaining in the final product, which affects the conductivity and stability of the coating layer; if the temperature is too high or the time is too long, an excessive reaction may be triggered, causing the structure of copper phosphide to be damaged, which is also not conducive to improving the material performance.
[0041] Moreover, appropriate heating temperature and holding time help to obtain a copper phosphide coating layer with good quality and stable structure. Under these conditions, copper phosphide crystals can grow orderly, forming a uniform and dense coating structure on the surface of lithium nickel cobalt manganese oxide. The uniform coating layer can effectively block the direct contact between the electrolyte and lithium nickel cobalt manganese oxide, reducing the dissolution of transition metal ions and the oxidation decomposition of the electrolyte; the dense structure enhances the conductivity and mechanical stability of the coating layer, and can stably exist and continuously play a protective role during the charge and discharge process of the battery, improving the cycle performance and overall stability of the positive electrode material.
[0042] As a preferred embodiment of the present invention, the molar ratio of phosphine to copper ions is 3 to 10:1 to ensure that there is sufficient phosphine participating in the reaction. If the amount of phosphine introduced is insufficient, that is, the molar ratio is less than 3:1, it will cause partial copper fluoride not to be reduced and remain in the final cathode material, affecting the electrochemical performance of the material, such as reducing conductivity and increasing the internal resistance of the battery. A suitable molar ratio helps to form a copper phosphide coating layer with excellent performance. An appropriate excess of phosphine (the upper limit of the molar ratio is 10:1) can ensure the formation of a continuous, uniform and dense copper phosphide coating layer on the surface of lithium nickel cobalt manganese oxide. This coating layer can better block the contact between the electrolyte and lithium nickel cobalt manganese oxide, effectively inhibit the oxidation decomposition of the electrolyte and the dissolution of transition metal ions, and thus improve the cycle stability and charge-discharge performance of the battery.
[0043] As a preferred embodiment of the present invention, the second heat treatment of the precursor under an inert atmosphere with the introduction of phosphine specifically includes: Refer to Figure 2 As shown, sodium dihydrogen phosphate and the precursor after the first heat treatment are respectively placed in a first crucible and a second crucible, and then the first crucible and the second crucible are placed in a heating furnace at a preset distance. The first crucible is located at the upwind position. Finally, the second heat treatment is carried out under an inert atmosphere. Sodium dihydrogen phosphate is decomposed by heat to produce phosphine, and copper fluoride is reduced by phosphine to produce copper phosphide.
[0044] Phosphine is a highly toxic, flammable and explosive gas. Directly introducing phosphine poses a great safety risk during the operation. Even a slight carelessness may lead to serious accidents such as poisoning and explosion. However, the method of generating phosphine by the thermal decomposition of sodium dihydrogen phosphate is carried out in a relatively closed heating furnace environment, and the generated phosphine directly participates in the reaction, reducing the leakage risk of phosphine in the external environment. At the same time, the presence of an inert atmosphere also further reduces the possibility of dangerous reactions between phosphine and oxygen, etc., providing a more reliable safety guarantee for the operators and the experimental environment.
[0045] In this preferred embodiment, in-situ generation of phosphine by sodium dihydrogen phosphate enables phosphine to react with copper fluoride instantly upon generation, reducing the possible loss or deterioration of phosphine in the air. Moreover, since phosphine is uniformly generated in the heating furnace and diffuses to the surface of the precursor, it is beneficial to form a more uniform and dense copper phosphide coating layer on the surface of lithium nickel cobalt manganese oxide. The uniform coating layer can more effectively block the contact between the electrolyte and lithium nickel cobalt manganese oxide, reduce the dissolution of transition metal ions, improve the cycle performance and stability of the cathode material, and thus improve the quality of the final product.
[0046] In this preferred embodiment, the decomposition rate of sodium dihydrogen phosphite can be adjusted by controlling the heating temperature and time, thereby precisely controlling the production amount and production rate of phosphine. In this way, the reaction between phosphine and copper fluoride can proceed more smoothly and orderly. In contrast, when directly introducing phosphine, it is more difficult to control the gas flow rate and pressure, and it is difficult to accurately match the reaction requirements. If the introduction speed is too fast, the reaction may be too violent to control; if the introduction speed is too slow, the reaction efficiency will be affected. This preferred embodiment effectively avoids these problems and ensures the controllability of the reaction.
[0047] As a preferred embodiment of the present invention, after the addition of the ammonium fluoride solution is completed, stirring is continued for 60 min to 180 min under the condition that the rotation speed is 300 rpm to 900 rpm.
[0048] In one embodiment, the present invention also discloses a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, which is prepared by using the above-mentioned preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, and includes lithium nickel cobalt manganese oxide and copper phosphide coated on the surface of the lithium nickel cobalt manganese oxide.
[0049] In one embodiment, the present invention also discloses an application of the above-mentioned copper phosphide-coated lithium nickel cobalt manganese oxide cathode material in a lithium-ion battery.
[0050] The following is an analysis and explanation in combination with specific examples.
[0051] Example 1, a preparation method of a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, which includes the following steps: S1, Dissolve 0.026 g of copper nitrate in 200 mL of water to obtain a copper nitrate solution, and then ultrasonically disperse 1.53 g of lithium nickel cobalt manganese oxide in the copper nitrate solution to obtain a first mixed solution.
[0052] S2, Slowly add 50 mL of an ammonium fluoride solution with a concentration of 0.0124 mol / L to the first mixed solution, continuously stir at a rotation speed of 900 rpm during the addition process, and continue to stir for 60 min after the addition is completed to obtain a second mixed solution.
[0053] S3, Centrifuge the second mixed solution, take the precipitate for washing and drying to obtain a precursor, which includes lithium nickel cobalt manganese oxide and NH4CuF3 formed by reaction on the surface of the lithium nickel cobalt manganese oxide.
[0054] S4, Perform the first heat treatment on the precursor in an argon atmosphere, set the heating temperature to 250 °C, set the heat preservation time to 420 min, and cool with the furnace to make NH4CuF3 decompose on the surface of the lithium nickel cobalt manganese oxide to generate copper fluoride.
[0055] S5. Place the precursor after the first heat treatment in the second crucible. Weigh 0.065 g of ammonium dihydrogen phosphite and place it in the first crucible. Then place the first crucible at the upper air inlet of the heating furnace about 30 cm away from the second crucible, and conduct the second heat treatment in an argon atmosphere. Set the heating temperature to 220 °C and the holding time to 240 min. After the second heat treatment is completed, sodium dihydrogen phosphite decomposes upon heating to produce phosphine, and copper fluoride is reduced by phosphine to form cuprous phosphide, finally obtaining the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material.
[0056] Example 2. A method for preparing a cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material, which comprises the following steps: S1. Dissolve 0.057 g of copper nitrate in 150 mL of water to obtain a copper nitrate solution. Then ultrasonically disperse 1.117 g of lithium nickel cobalt manganese oxide in the copper nitrate solution to obtain a first mixed solution.
[0057] S2. Slowly add 50 mL of an ammonium fluoride solution with a concentration of 0.036 mol / L dropwise to the first mixed solution, continuously stir at a speed of 300 rpm during the dropping process, and continue to stir for 180 min after the dropping is completed to obtain a second mixed solution.
[0058] S3. Centrifuge the second mixed solution, take the precipitate, wash and dry it to obtain a precursor, which includes lithium nickel cobalt manganese oxide and NH4CuF3 formed by reaction on the surface of the lithium nickel cobalt manganese oxide.
[0059] S4. Conduct the first heat treatment on the precursor in an argon atmosphere. Set the heating temperature to 300 °C and the holding time to 120 min, and cool it in the furnace to make NH4CuF3 decompose on the surface of the lithium nickel cobalt manganese oxide to form copper fluoride.
[0060] S5. Place the precursor after the first heat treatment in the second crucible. Weigh 0.21 g of ammonium dihydrogen phosphite and place it in the first crucible. Then place the first crucible at the upper air inlet of the heating furnace about 30 cm away from the second crucible, and conduct the second heat treatment in an argon atmosphere. Set the heating temperature to 300 °C and the holding time to 120 min. After the second heat treatment is completed, sodium dihydrogen phosphite decomposes upon heating to produce phosphine, and copper fluoride is reduced by phosphine to form cuprous phosphide, finally obtaining the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material.
[0061] Comparative example. Lithium nickel cobalt manganese oxide cathode material without coating treatment.
[0062] Conduct cyclic performance tests on the products of Example 1, Example 2 and the comparative example respectively. The results are shown in Figure 3 .
[0063] The uncoated lithium nickel cobalt manganese oxide cathode material described in the comparative example had an initial discharge specific capacity of 169.3 mAh / g at a high temperature of 55 °C in the voltage range of 2.8 V to 4.5 V. After 100 cycles of constant current charge and discharge at a rate of 1C, the discharge specific capacity was 118.8 mAh / g, and the capacity retention rate was 70.17%.
[0064] The product obtained in Example 1 had an initial discharge specific capacity of 173 mAh / g at a high temperature of 55 °C in the voltage range of 2.8 V to 4.5 V. After 100 cycles of constant current charge and discharge at a rate of 1C, the discharge specific capacity was 146.5 mAh / g, and the capacity retention rate was 84.68%.
[0065] The product obtained in Example 2 had an initial discharge specific capacity of 171.6 mAh / g at a high temperature of 55 °C in the voltage range of 2.8 V to 4.5 V. After 100 cycles of constant current charge and discharge at a rate of 1C at a high temperature of 55 °C, the discharge specific capacity was 138.6 mAh / g, and the capacity retention rate was 80.76%.
[0066] By comparison, the capacity retention rates of Example 1 and Example 2 were both higher than that of the comparative example, indicating that the preparation of the cuprous phosphide coating layer can effectively improve the cycling performance of the lithium nickel cobalt manganese oxide cathode material.
[0067] The above embodiments are only preferred embodiments given to fully illustrate the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or transformations made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention.
Claims
1. A preparation method of a copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, characterized in that, It includes: Disperse lithium nickel cobalt manganese oxide in a copper ion salt solution to obtain a first mixed solution; Dropwise add an ammonium fluoride solution to the first mixed solution and continuously stir to obtain a second mixed solution; Centrifuge the second mixed solution, take the precipitate, wash and dry it to obtain a precursor, which includes lithium nickel cobalt manganese oxide and NH4CuF3 formed by reaction on the surface of the lithium nickel cobalt manganese oxide; Conduct a first heat treatment on the precursor under an inert atmosphere, and NH4CuF3 decomposes on the surface of the lithium nickel cobalt manganese oxide to form copper fluoride; Then conduct a second heat treatment on the precursor under an inert atmosphere and in the presence of phosphine, and the copper fluoride is reduced by phosphine to form cuprous phosphide, that is, the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material is obtained.
2. The preparation method of the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: The copper ion salt solution is a copper nitrate solution, a copper sulfate solution or a copper chloride solution; The concentration of the copper ion salt solution is 0.001 mol / L to 0.01 mol / L; In the first mixed solution, the molar ratio of lithium nickel cobalt manganese oxide to copper ions is 25 to 76:
1.
3. The preparation method of the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, characterized in that: The concentration of the ammonium fluoride solution is 0.01 mol / L to 0.05 mol / L; In the second mixed solution, the molar ratio of ammonium fluoride to copper ions is 2 to 4:
1.
4. The preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: The heating temperature of the first heat treatment is set to 250 °C to 300 °C, and the heat preservation time is set to 120 min to 420 min.
5. The preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: The heating temperature of the second heat treatment is set to 220 °C to 300 °C, and the heat preservation time is set to 120 min to 240 min.
6. The preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: The molar ratio of the phosphine to the copper ions is 3 to 10:
1.
7. The preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: Conducting the second heat treatment on the precursor under an inert atmosphere and in the presence of phosphine specifically includes: placing sodium dihydrogen phosphite and the precursor after the first heat treatment in a first crucible and a second crucible respectively, then placing the first crucible and the second crucible in a heating furnace at a preset distance, with the first crucible located at the upwind position, and finally conducting the second heat treatment under an inert atmosphere. The sodium dihydrogen phosphite decomposes upon heating to produce phosphine, and the copper fluoride is reduced by the phosphine to form cuprous phosphide.
8. The preparation method of the copper phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 1, wherein: After the dropwise addition of the ammonium fluoride solution is completed, continue to stir for 60 min to 180 min at a rotation speed of 300 rpm to 900 rpm.
9. A copper phosphide-coated lithium nickel cobalt manganese oxide cathode material, characterized in that: Prepared by using the preparation method of the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material according to any one of claims 1 to 8, including lithium nickel cobalt manganese oxide and cuprous phosphide coated on the surface of the lithium nickel cobalt manganese oxide.
10. Application of the cuprous phosphide-coated lithium nickel cobalt manganese oxide cathode material according to claim 9 in a lithium ion battery.